2008
DOI: 10.1021/ac800591j
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative LC−MS of Polymers: Determining Accurate Molecular Weight Distributions by Combined Size Exclusion Chromatography and Electrospray Mass Spectrometry with Maximum Entropy Data Processing

Abstract: We report on the successful application of size exclusion chromatography (SEC) combined with electrospray ionization mass spectrometry (ESI-MS) and refractive index (RI) detection for the determination of accurate molecular weight distributions of synthetic polymers, corrected for chromatographic band broadening. The presented method makes use of the ability of ESI-MS to accurately depict the peak profiles and retention volumes of individual oligomers eluting from the SEC column, whereas quantitative informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
153
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 69 publications
2
153
0
1
Order By: Relevance
“…74 From a chemical point of view, the latter option seems advantageous, because no addition of a controlling or regulating agent is required to artificially suppress the molecular weights. However, the interpretation and reproducible generation of ESI-MS spectra of high charge states is complex and does not lend itself to the throughput of large amounts of samples.…”
Section: Mass Spectrometry Of Acrylate Polymersmentioning
confidence: 99%
“…74 From a chemical point of view, the latter option seems advantageous, because no addition of a controlling or regulating agent is required to artificially suppress the molecular weights. However, the interpretation and reproducible generation of ESI-MS spectra of high charge states is complex and does not lend itself to the throughput of large amounts of samples.…”
Section: Mass Spectrometry Of Acrylate Polymersmentioning
confidence: 99%
“…The mass spectrometer was coupled to the column in parallel to an RIdetector (G1362A with SS420x A/D) in a setup described previously. [19] Eluent (0.27 mL Á min À1) was directed through the RI-detector and 30 mL Á min À1 infused into the electrospray source after post-column addition of a 100 mM solution of sodium trifluoroacetate in methanol at 20 mL Á min À1 by a micro-flow HPLC syringe pump (Teledyne ISCO, Model 100DM). A polymer solution (10 mL) with a concentration of 2 mg Á mL À1 was injected onto the HPLC system.…”
Section: Sec-esi-msmentioning
confidence: 99%
“…[18] Therefore, the analysis is usually limited to samples with molecular weights below 2-3 kDa. Despite of this, Gruendling et al [19] and Aaserud et al [20] have shown that this problem can be alleviated by coupling ESI-MS to size exclusion chromatography (SEC), effectively broadening the analyzable mass range of polymers exhibiting multiple charging. In offline LC-MS, optimization is performed easily, as the prefractionated sample can be introduced into the mass spectrometer almost indefinitely in a repetitive fashion.…”
mentioning
confidence: 99%
“…[ 41 ] A 0.27 mL·min −1 aliquot of the eluent was directed through the RI detector and 30 μL·min −1 infused into the electrospray source after postcolumn addition of a 0.1mM solution of sodium iodide in methanol at 20 μL·min −1 by a micro fl ow HPLC syringe pump (Teledyne ISCO, Model 100DM). The polymer solutions (20 μL) with a concentration of ∼ 2 mg·mL −1 were injected into the HPLC system.…”
Section: Methodsmentioning
confidence: 99%